Synthesis and biological evaluation of potential acetylcholinesterase inhibitors based on a benzoxazine core. Issue 5 (3rd April 2018) - Méndez‐Rojas, Claudio; Quiroz, Gabriel; Faúndez, Mario; Gallardo‐Garrido, Carlos; Pessoa‐Mahana, C. David; Chung, Hery; Gallardo‐Toledo, Eduardo; Saitz‐Barría, Claudio; Araya‐Maturana, Ramiro; Kogan, Marcelo J.; Zúñiga‐López, María C.; Iturriaga‐Vásquez, Patricio; et al.
Abstract: With the purpose of expanding the structural variety of chemical compounds available as pharmacological tools for the treatment of Alzheimer's disease, we synthesized and evaluated a novel series of indole‐benzoxazinones (Family I ) and benzoxazine‐arylpiperazine derivatives (Family II ) for potential human acetylcholinesterase ( h AChE) inhibitory properties. The most active compounds 7a and 7d demonstrated effective inhibitory profiles with K i values of 20.3 ± 0.9 μM and 20.2 ± 0.9 μM, respectively. Kinetic inhibition assays showed non‐competitive inhibition of AChE by the tested compounds. According to our docking studies, the most active compounds from both series (Families I and II ) showed a binding mode similar to donepezil and interact with the same residues. Abstract : A series of novel indole‐benzoxazinones and benzoxazine‐arylpiperazine derivatives were synthesized and evaluated for their human acetylcholinesterase ( h AChE) inhibitory properties. Compounds 7a and 7d demonstrated effective inhibitory profiles with K i values of 20.3 ± 0.9 and 20.2 ± 0.9 μM, respectively.